(untitled) (Journal of Chemical Engineering, 2014)
The present study focuses potentiality of biodiesel production in Bangladesh from non-edible oil. The increasing demands of energy are consumed by using fossil fuels which are non-renewable and will be depleted within 150 years from now if this growth rate stays but if this rate increases further the depleting time will decrease from the estimated one. Because of low reservation of crude oil, Bangladesh has to import oils from other countries, these costs a lot. About 95% of these demands can be meted through biodiesel. Biodiesel prepared from both edible and non-edible oils. After meeting demands of edible oil of the country it is impossible to produce biodiesel from edible oils. But it is possible to meet the biodiesel demand of the country almost 100% through non-edible oil derived biodiesel. Arable lands of Bangladesh cant be used for the growing purposes of non-edible oil seeds, but if rail and road sides are used there is no need for extra lands. After surveying lands for this purpose it seems that Bangladesh can get a total amount of 47750 Km of road and rail side areas for the cultivation of non-edible seeds. Among these forest seeds Nageswar, Pitraj, Sultana champa Ponyal, Rata, Oil palm, Chaulmoogra, Bakul, Kusum, jaina have sufficient oil content along with plenty of growth in Bangladesh. Cultivating these seeds 1100000 tones of biodiesel can be produced on the basis of their oil content and yield. Which decreases the amount of imported crude oil as well as meets the oil demand of the country, thus Bangladesh can be able to save about 6 billion per year means a great economic savings that can be used for the development of the country. DOI: http://dx.doi.org/10.3329/jce.v27i2.17763 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 2, June 2012: 1-5